2016
DOI: 10.1371/journal.pcbi.1005240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lipid Composition and Receptor Conformation on the Spatio-temporal Organization of μ-Opioid Receptors in a Multi-component Plasma Membrane Model

Abstract: The lipid composition of cell membranes has increasingly been recognized as playing an important role in the function of various membrane proteins, including G Protein-Coupled Receptors (GPCRs). For instance, experimental and computational evidence has pointed to lipids influencing receptor oligomerization directly, by physically interacting with the receptor, and/or indirectly, by altering the bulk properties of the membrane. While the exact role of oligomerization in the function of class A GPCRs such as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 83 publications
5
49
0
Order By: Relevance
“…These nanoclusters are in dynamic equilibrium, with constant aggregation and dissociation to generate new receptor complexes (Calebiro et al, 2013). Many factors are involved in the regulation of GPCR nanoclustering (Calebiro et al, 2013;Hauser et al, 2016), including transmembrane proteins (Bethani et al, 2010), cell membrane lipid composition (Marino et al, 2016), and the actin cytoskeleton (Scarselli et al, 2012), which regulates trafficking of signaling molecules and partitions the membrane into microdomains (Kusumi et al, 2005). Nanoclustering and dynamics are especially relevant for chemokine receptors, as they allow the cell to correctly sense gradients and move appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoclusters are in dynamic equilibrium, with constant aggregation and dissociation to generate new receptor complexes (Calebiro et al, 2013). Many factors are involved in the regulation of GPCR nanoclustering (Calebiro et al, 2013;Hauser et al, 2016), including transmembrane proteins (Bethani et al, 2010), cell membrane lipid composition (Marino et al, 2016), and the actin cytoskeleton (Scarselli et al, 2012), which regulates trafficking of signaling molecules and partitions the membrane into microdomains (Kusumi et al, 2005). Nanoclustering and dynamics are especially relevant for chemokine receptors, as they allow the cell to correctly sense gradients and move appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Recent CG simulations using bilayers composed of multiple lipid species have provided insights into GPCR-lipid interactions in a more biologically realistic environment (Ingolfsson et al, 2014;Koldso and Sansom, 2015). For example, the m-opioid receptor embedded in a complex lipid membrane was shown to induce lipid regions with high-order near certain transmembrane helices that may facilitate receptor dimerization (Marino et al, 2016). However, it remains unclear how GPCR-lipid interactions modulate the functions of GPCRs, such as receptor activation and downstream signaling, in a physiologically relevant context (i.e., in a lipid bilayer environment mimicking a mammalian cell membrane).…”
Section: Introductionmentioning
confidence: 99%
“…Capturing the oligomerization of GPCRs currently requires a coarse‐grained (CG) model, that is, a reduced representation with one bead describing multiple heavy atoms, since all‐atom MD simulations would be too computationally expensive. The MARTINI CG model has been used to study self‐assembly of a number of GPCRs, including opioid receptors (Provasi et al , ; Marino et al , ), rhodopsin (Periole et al , ; ), β 2 adrenoceptors (Prasanna et al , ) and the chemokine receptor CCR4 (Pluhackova et al , ). All‐atom MD has thus far only been applied to the preformed crystallographic dimers of the μ receptor and not their free association (Shim et al , ; Huang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, experiments have clearly shown that μ receptor oligomerization is sensitive to cholesterol levels (Zheng et al , ) and modulating serum cholesterol levels has been shown to affect the analgesic profile of opioids (Huang et al , ). To examine the effect of the lipids on opioid receptor oligomerization, we (Marino et al , ) recently examined the supramolecular organization of the inactive and/or activated conformations of the μ receptor in a 63‐component idealized plasma membrane model (Ingólfsson et al , ). These simulations suggested a specific mechanism by which lipid molecules appear to regulate the dimerization process of opioid receptors.…”
Section: Introductionmentioning
confidence: 99%